What Can Economists Explain by Taking into Account People's Perceptions of Fairness? Punishing Cheats, Bargaining Impasse, and Self-Perpetuating Inequalities - Hoff, Karla (Washington, DC: World Bank, 2012)
A standard hypothesis in economics, the rational self-interest hypothesis, is based on a radically simplified view of human nature that says individuals are exclusively motivated by their material self-interest and unboundedly rational in the pursuit of it. Yet experimental evidence overwhelmingly refutes this hypothesis. Evidence abounds that individuals have preferences for being treated and treating others fairly. These preferences do not affect economic outcomes in competitive markets with standardized products but do affect economic outcomes in a wide variety of other settings where information is imperfect or enforcement is costly. Also discussed are 1) how preferences for fairness can solve a free rider problem, 2) the pitfalls of human concern for fairness, and 3) how extreme inequality can be perpetuated through belief systems that represent oppression as "fair".